Maternal knowledge, food restriction and prevention strategies related to anaemia in pregnancy: a cross-sectional study - Ekwere, Timothy A.; Ekanem, Anyiekere M. (International Journal Of Community Medicine And Public Health, 2017)
Background: Anaemia is a major cause of morbidity and mortality among pregnant women in developing countries including Nigeria, affecting about 33% - 75% of all pregnant women. The burden and predisposing factors varies even within countries. Methods:A cross sectional descriptive was conducted; participants were recruited using consecutive sampling technique. Data were obtained from study consented participants using pretested self-administered questionnaire and analyzed using SPSS for Windows Version 17.0. Significant level was set at p < 0.05. Results: A total of 121 pregnant women with a mean age of 25.69±4.51 years participated in the study. Majority had post-primary education. The women exhibited good knowledge of anaemia in pregnancy. However, restriction of food including those rich in carbohydrates, proteins and alcoholic beverages (27.3%, 14.9%, and 56.8% respectively) was a common practice. Customs and religious beliefs were a major influence on food restrictions (50.8% and 28% respectively). Iron and folate supplementation, balanced diet, use of long lasting insecticide net, regular ante natal clinic visits among others were strategies respondents believes could help mitigate against this condition. Conclusions:The respondents had good knowledge of anaemia in pregnancy. However, restriction of nutritious food other than alcoholic beverages by significant proportion of the respondents is a cause for concern as this is a potential risk for anaemia in pregnancy. Nutrition education should be enhanced and sustained.